2018
DOI: 10.1016/j.jtcvs.2017.07.074
|View full text |Cite
|
Sign up to set email alerts
|

Survival and recurrence after acute pulmonary embolism treated with pulmonary embolectomy or thrombolysis in New York State, 1999 to 2013

Abstract: Pulmonary embolectomy and thrombolysis are associated with similar early and long-term survival, supporting guideline recommendations for embolectomy when thrombolysis is contraindicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 22 publications
0
57
1
1
Order By: Relevance
“…Surgical embolectomy in acute PE is usually carried out with cardiopulmonary bypass, without aortic cross-clamping and cardioplegic cardiac arrest, followed by incision of the two main pulmonary arteries with the removal or suction of fresh clots. Recent reports have indicated favourable surgical results in high-risk PE, with or without cardiac arrest, and in selected cases of intermediate-risk PE [297][298][299][300]. Among 174 322 patients hospitalized between 1999 and 2013 with a diagnosis of PE in New York state, survival and recurrence rates were compared between patients who underwent thrombolysis (n=1854) or surgical embolectomy (n=257) as first-line therapy [297].…”
Section: Surgical Embolectomymentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical embolectomy in acute PE is usually carried out with cardiopulmonary bypass, without aortic cross-clamping and cardioplegic cardiac arrest, followed by incision of the two main pulmonary arteries with the removal or suction of fresh clots. Recent reports have indicated favourable surgical results in high-risk PE, with or without cardiac arrest, and in selected cases of intermediate-risk PE [297][298][299][300]. Among 174 322 patients hospitalized between 1999 and 2013 with a diagnosis of PE in New York state, survival and recurrence rates were compared between patients who underwent thrombolysis (n=1854) or surgical embolectomy (n=257) as first-line therapy [297].…”
Section: Surgical Embolectomymentioning
confidence: 99%
“…Recent reports have indicated favourable surgical results in high-risk PE, with or without cardiac arrest, and in selected cases of intermediate-risk PE [297][298][299][300]. Among 174 322 patients hospitalized between 1999 and 2013 with a diagnosis of PE in New York state, survival and recurrence rates were compared between patients who underwent thrombolysis (n=1854) or surgical embolectomy (n=257) as first-line therapy [297]. Overall, there was no difference between the two types of reperfusion treatment regarding 30 day mortality (15 and 13%, respectively), but thrombolysis was associated with a higher risk of stroke and re-intervention at 30 days.…”
Section: Surgical Embolectomymentioning
confidence: 99%
“…As we previously wrote, recent reports highlighting improved surgical techniques have shown that surgical pulmonary embolectomy yields similar 30-day and 5-year mortality rates compared to thrombolytic therapy. 5,6 However, compared to thrombolysis, surgical pulmonary embolectomy was associated with lower rates of bleeding complications, stroke, and requirement for re-intervention within 30 days. 6 Our introduction of the MIPE via a left mini thoracotomy highlights an advancement in surgical embolectomy in that it avoids sternotomy and related complications allowing for enhanced recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, cardioplegic cardiac arrest with cardiopulmonary bypass is usually necessary. In comparison to systemic thrombolysis, Lee et al reported similar survival rates and a lower risk of stroke [14]. However, surgical embolectomy showed the highest mortality rates (32%) after cardiac arrest [15].…”
Section: Introductionmentioning
confidence: 99%